Analisis Keadilan Hukum Putusan Verstek Pada Perkara Cerai Talak No. 0520/Pdt.G/2014/PA. Kab. Kediri - Abdullah Taufik (MAHAKIM Journal of Islamic Family Law, 2019)
Verstek’s decision is a decision handed down by the judge without the presence of the defendant or respondent at the trial, the principle that the judge is authorized to make a decision or not without the presence of the defendant at the trial so that the judge has facultative rights, in this case referring to article 126 HIR (about verstek) as a reference: 1. The absence of the defendant at the first hearing that authorized the judgeimmediately to decide on the verstek 2. Delay the session and call the defendant once again. In such legal cases / events, the position of the defendant / defendant in the divorce case is always in a weak position, especially if the respondent is a woman, with all her limitations she will always be passive and difficult to provide resistance is most likely caused by the following factors: a. Unclear address; b. The call (relas) for the trial does not arrive; c. Lack of understanding procedures in court proceedings and reluctance to consult; d. More resigned and accept fate